Investigating TiO2–HA–PCL hybrid coating as an efficient corrosion resistant barrier of ZM21 Mg alloy - Navdeep Singh; Uma Batra; Kamal Kumar; Anil Mahapatro (Journal of Magnesium and Alloys, 2021)
Surface modification for improving corrosion resistance of Mg alloys is highly demanded for degradable orthopedic and cardiovascular devices. The research reports the design and development of TiO2HA composite and novel TiO2HA–PCL hybrid coating belonging to the unique class of inorganic organic hybrid with striking features that are explored for the first time in the corrosion resistance of Mg alloys. Sol–gel dip coating combined with non-solvent induced phase separation is used to create the hybrid coating. TiO2HA–PCL hybrid coating introduces strong hydrogen bonding between TiO2HA inorganic matrix and PCL organic layer in addition to the Vander wall electrostatic interaction of the later with the Mg substrate which in turn enhance adhesion strength to about 1.5 times of TiO2HA coating. The corrosion potentials for TiO2HA–PCL and TiO2HA were found to be −0.407 V and −1.017 V (vs Ag/AgCl), respectively. The current densities of TiO2HA–PCL and TiO2HA were found to be 7.31 × 10−8 A/cm2 and 4.03 × 10−4 A/cm2 respectively. The corrosion resistance of coatings was confirmed by immersion testing by weight loss, pH changes and H2 evolution measurements at interval of 7 days till 28 days. The present TiO2HA–PCL coating in comparison to TiO2HA coating demonstrate nearly 6% less weight loss. The outcome of the present work was compared with the similar coatings in recent past. The work done ingresses enhancing the corrosion resistance of Mg alloys, which fulfill the dreams of future degradable orthopedic and cardiovascular devices.